2020
DOI: 10.1080/19490976.2020.1738187
|View full text |Cite
|
Sign up to set email alerts
|

Maternal sucralose intake alters gut microbiota of offspring and exacerbates hepatic steatosis in adulthood

Abstract: Background: Nonalcoholic fatty liver disease (NAFLD) is considered to be associated with diet and gut dysbiosis. Excessive sucralose can induce gut dysbiosis and negatively affect host health. Maternal diet shapes the microbial communities of neonate and this effect continues in later life. We aimed to investigate the effects of maternal sucralose (MS) intake on the susceptibility of offspring to hepatic steatosis in adulthood. Methods: C57BL/6 pregnant mice were randomized into MS group (MS during gestation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 74 publications
2
47
0
3
Order By: Relevance
“…An adequate physical gut barrier consists of a mucous layer, intestinal epithelial cells, and tight junctions [ 29 ]. It is pivotal for protection against the potentially harmful compounds and microorganisms while promoting the absorption of nutrients, electrolytes, and water.…”
Section: Resultsmentioning
confidence: 99%
“…An adequate physical gut barrier consists of a mucous layer, intestinal epithelial cells, and tight junctions [ 29 ]. It is pivotal for protection against the potentially harmful compounds and microorganisms while promoting the absorption of nutrients, electrolytes, and water.…”
Section: Resultsmentioning
confidence: 99%
“…NAFLD in children is a major risk factor for the development of cirrhosis and hepatocellular carcinoma in adult [ 2 , 3 ], and it is also an early predictor of hypertension and type 2 diabetes [ 4 , 5 ]. Pregnancy is a critical period for fetal organ development [ 6 ], and maternal diet during pregnancy plays an important role in protecting against or exacerbating the offspring’s risk of developing NAFLD [ 7 , 8 ]. Emerging evidence from human and animal studies has revealed that a high-salt (HS) diet in adulthood is not only a major risk factor for hypertension [ 9 ] and cardiovascular disease [ 10 ], but also exerts effects on hypertriglyceridemia [ 11 ], oxidative stress, and inflammation [ 12 ], which are well-known pathological features of the development of NAFLD [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Maternal obesity and high-fat diet consumption both alter the gut microbiota of their offspring and increase their risk of developing NAFLD (168,169). Therefore, interventions that target mothers are one approach for preventing NAFLD in children.…”
Section: Gut Microbiota-targeted Preventives and Treatments For Nafldmentioning
confidence: 99%